PENGARUH IMPLEMENTASI AI PADA SISTEM INFOMASI MANAJEMEN - Manalu, Jhon Kristopel; Dian Eka Matra Putra Bangun; Darwis Manalu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The current development of digital technology has driven a significant transformation in information management, one of which is the application of artificial intelligence in management information systems, providing effectiveness and efficiency in business processes. The integration of artificial intelligence and management information systems has transformed procedures for collecting, analyzing, utilizing, and utilizing data, as well as organizational decision-making processes. Management Information Systems (MIS) are strategic elements that integrate data, technology, and processes to support organizational competitiveness. This study aims to provide an understanding of the concept, benefits, and role of MIS in supporting digital transformation. This research is expected to provide insight and knowledge about the role of MIS in supporting managerial functions such as planning, organizing, controlling, and speeding up decision-making. MIS can support organizational performance in achieving organizational goals in today's digital era.